SELECTION OF EUCALYPTUS CLONES AND ADJUSTMENT OF POTASSIUM DOSES FOR EXTENDED DROUGHT IN BAHIA SAVANNA - Sampaio, Thalita Fernanda [UNESP]; Dalcin, Tiago Elias; Bogiani, Julio Cesar; Mori, Edson Seizo [UNESP]; Guerrini, Irae Amaral [UNESP] (Univ Federal Vicosa, 2016)
The use of clones adapted to regions with water deficit caused by well-defined and prolonged dry periods, as happens in the western part Bahia, is a way to overcome water stress. The adjustment of potassium (K) also influences this aspect, because it regulates the opening and closing of stomata, impeding water loss by plants and making them more efficient in water use. Therefore, the aim of this study was to evaluate the performance of eucalyptus clones grown for energy production in response to potassium levels in soil and climate conditions, in the municipality of Luis Eduardo Magalhaes, located in western Bahia state. A randomized block with four replications in a split plot was used as experimental design. Six eucalyptus clones (AEC-056, CEA-144, CEA-220, CEA-224, CEA-103 and CEA-1528) and four doses of K2O (0, 30, 60 and 120 kg ha(-1)) were tested. At two years old, clone 1528 showed greatest productivity, with the tallest height and trunk diameter, while 056 showed the lowest performance. Different K requirements were observed among eucalyptus clones for both growth and productivity.
Keywords: Water deficit; Eucalyptus growth; Potassium fertilization